2021
DOI: 10.47203/ijch.2021.v33i01.024
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and utilisation of quitline among current tobacco users in a district in southern india

Abstract: Background: Tobacco use not only increases mortality, but also causes enormous burden to the Nation’s health and economy. The WHO -Framework Convention on Tobacco Control implemented “MPOWER”, comprising of an important entity of ‘offering help to tobacco users’ to quit. Quitline provides evidence-based treatment services to tobacco users and advertising those services has the potential to increase their utilisation. Objectives: Our objective was to assess the awareness and utilisation of the newly introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Even with the developing infrastructure and facilities toward tobacco cessation, the study results indicated that smokers or SLT users did not translate into successful quitters as the quit rates continue to remain low (<5% in males and <2% in females) in GATSs. A study highlighted that there is a lack of awareness and utilization of the national quit-line services in India among tobacco users, and illiteracy and poor education make it unusable 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the developing infrastructure and facilities toward tobacco cessation, the study results indicated that smokers or SLT users did not translate into successful quitters as the quit rates continue to remain low (<5% in males and <2% in females) in GATSs. A study highlighted that there is a lack of awareness and utilization of the national quit-line services in India among tobacco users, and illiteracy and poor education make it unusable 29…”
Section: Discussionmentioning
confidence: 99%
“…A study highlighted that there is a lack of awareness and utilization of the national quit-line services in India among tobacco users, and illiteracy and poor education make it unusable. 29 Therefore, India being a highly prevalent and major tobacco-producing country needs newer strategies to bridge the education gap along with incorporating digital health mediums for larger cessation impacts. Furthermore, evidence-based intervention programs, such as the Tobacco Free Teachers-Tobacco Free Schools (TFT-TFS) program, 30 can be utilized and incorporated into current national Tobacco-Free Educational Institution (ToFEI) guidelines for the prevention of tobacco use among school personnel, adolescents, and their parents.…”
Section: O: Offer Help To Quit Tobacco Usementioning
confidence: 99%